(3GdCTYKjGJs - (3Gdchaj, CHh GdMSf, eMeO Hf eMeO Hf GdGTYK Hf eMeO, cGf MjG(B: 313(3g`s ((3eMeO HGbQ eMeO GdUOJheGfjs)
(3ChdgG (B:s
(3CNHQfG GdTjN CHh GdMSf CMeO Hf GdeXaQ (B... (3HGH WgGQI GdeGAs
(3BNQgG (B:s
(3CNHQfG YHO Gddg Hf eMeO CNHQfG eMeO Hf eMeO (B... (3Cf GdfHj cGf jYhP GdMSf hGdMSjf YdjgeG GdSdGe(B... (3BNQ cJGH GdSff hGdMeO ddg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B627s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B627s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs